2017
DOI: 10.7554/elife.26602
|View full text |Cite
|
Sign up to set email alerts
|

Induced sensorimotor cortex plasticity remediates chronic treatment-resistant visual neglect

Abstract: Right brain injury causes visual neglect - lost awareness of left space. During prism adaptation therapy, patients adapt to a rightward optical shift by recalibrating right arm movements leftward. This can improve left neglect, but the benefit of a single session is transient (~1 day). Here we show that tonic disinhibition of left motor cortex during prism adaptation enhances consolidation, stabilizing both sensorimotor and cognitive prism after-effects. In three longitudinal patient case series, just 20 min o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 74 publications
8
95
4
Order By: Relevance
“…In healthy individuals, rightward PA increased BOLD response in the left inferior parietal cortex 30 . Our cortical thickness and diffusion results suggest an implication of left prefrontal cortex in prism-induced neglect compensation, consistent with the observation that effective PA in neglect is facilitated by TMS-based disinhibition of the left motor cortex 31 . Altogether, these findings fit well with the fronto-parietal organization of attention networks in the primate brain 32 .…”
Section: Discussionsupporting
confidence: 90%
“…In healthy individuals, rightward PA increased BOLD response in the left inferior parietal cortex 30 . Our cortical thickness and diffusion results suggest an implication of left prefrontal cortex in prism-induced neglect compensation, consistent with the observation that effective PA in neglect is facilitated by TMS-based disinhibition of the left motor cortex 31 . Altogether, these findings fit well with the fronto-parietal organization of attention networks in the primate brain 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Here we exploit this variation to test a causal mechanistic hypothesis about how sensorimotor memories in human brain are formed, retained and enhanced. Primary motor cortex (M1) has been identified as a critical region for the maintenance of newly acquired visuomotor maps following sensorimotor adaptation in both primates (Wise et al 1998;Li et al 2001;Paz et al 2003;Paz et al 2005;Inoue et al 2016) and humans (Hadipour-Niktarash et al 2007;Hunter et al 2009;Galea et al 2010;Landi et al 2011;Leow et al 2016;O'Shea et al 2017). We previously demonstrated that left M1 anodal transcranial direct current stimulation (a-tDCS) applied during adaptation to a 10-degree rightward displacement of the visual field (prism adaptation, PA) enhances consolidation of the prism after-effect (AE) in the healthy brain .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the size of the voxel, adjacent regions of sensory cortex (S1) were also included in the measure of M1 metabolites. This is a common methodological limitation of MRS studies (Stagg et al 2009;Lunghi et al 2015;Antonenko et al 2017;Ip et al 2017;Kolasinski et al 2017;O'Shea et al 2017). Although we cannot rule out the contribution of S1 to our results, M1 is likely to play a predominant role because of a convergence of studies implicating it in the consolidation of adaptation memory (Wise et al 1998;Li et al 2001;Paz et al 2003;Paz et al 2005;Hadipour-Niktarash et al 2007;Landi et al 2011;Leow et al 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations